Successful Replication of "The Long-Run Effects of Sports Club Vouchers for Primary School Children (2022)" - Felix Bacon; Abdel-Hamid Bello; Myriam Brown; Todd Morris; Laëtitia Renée (Institute for Replication (I4R), 2023)
Marcus, Siedler and Ziebarth (2022 American Economic Journal: Economic Policy) examine the long-run health effects of a universal sports-club voucher program that was introduced in Saxony for primary school children in 2009. In 2018, the authors designed a survey that targeted the affected cohorts and nearby cohorts in Saxony and two neighboring states, and use a differences-in-differences identification strategy that exploits variation across states and cohorts in policy exposure. The authors document that treated individuals have knowledge of the program and recall receiving and redeeming the vouchers at higher rates, but find no effects on any health outcomes or behaviors. We successfully reproduce the main results of the paper exactly using data available in the paper's replication package and new Stata and R code. We also verify the robustness of the results using different outcomes, different control variables, different sample restrictions and different inference methods.
Keywords: 330